A bride's story. 14 - Mori, Kaoru, 1978- (Yen Press, 2023)
"The Halgals enter talks of marriage with another clan, but first, Azel and the other men must be tested to see if they are worthy. They face off against their prospective brides in a horse-riding competition, and whoever retrieves an arrow and makes it to the finish line first will hold the future of both clans in their hands!"--